Desmoid tumor in patients with familial adenomatous polyposis - Leal,Raquel Franco (2010)
CONTEXT: Desmoid tumors constitute one of the most important extraintestinal manifestations of familial adenomatous polyposis. The development of desmoids is responsible for increasing morbidity and mortality rates in cases of familial adenomatous polyposis. OBJECTIVES: To evaluate the occurrence of desmoid tumors in familial adenomatous polyposis cases following prophylactic colectomy and to present patient outcome. METHODS: Between 1984 and 2008, 68 patients underwent colectomy for familial adenomatous polyposis at the School of Medical Sciences Teaching Hospital, University of Campinas, SP, Brazil. Desmoid tumors were found in nine (13.2%) of these patients, who were studied retrospectively by consulting their medical charts with respect to clinical and surgical data. RESULTS: Of nine patients, seven (77.8%) were submitted to laparotomy for tumor resection. Median age at the time of surgery was 33.9 years (range 22-51 years). Desmoid tumors were found in the abdominal wall in 3/9 cases (33.3%) and in an intra-abdominal site in the remaining six cases (66.7%). Median time elapsed between ileal pouch-anal anastomosis and diagnosis of desmoid tumor was 37.5 months (range 14-60 months), while the median time between colectomy with ileorectal anastomosis and diagnosis was 63.7 months (range 25-116 months). In 6/9 (66.7%) patients with desmoid tumors, the disease was either under control or there was no evidence of tumor recurrence at a follow-up visit made a mean of 63.1 months later (range 12-240 months). CONCLUSIONS: Desmoid tumors were found in 13.2% of cases of familial adenomatous polyposis following colectomy; therefore, familial adenomatous polyposis patients should be followed-up and surveillance should include abdominal examination to detect signs and symptoms. Treatment options include surgery and clinical management with antiestrogens, antiinflammatory drugs or chemotherapy.